2002
DOI: 10.1063/1.1496457
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics study of proton mobility in liquid methanol

Abstract: The transport of protons through aqueous, partially aqueous, or nonaqueous hydrogen-bonded media is a fundamental process in many biologically and technologically important systems. Liquid methanol is an example of a hydrogen-bonded system that, like water, supports anomalously fast proton transport. Using the methodology of ab initio molecular dynamics, in which internuclear forces are computed directly from electronic structure calculations as the simulation proceeds, we have investigated the microscopic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
148
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 80 publications
11
148
0
3
Order By: Relevance
“…The failure of AN to propagate LR-SIE confirms our conjecture, but the experiments in IPA appear to contradict it. However, we consider that the latter result represents a false negative because IPA, in contrast with H 2 O and MeOH, [49][50][51][52][53][54][55][56] lacks an extensive H-bond network. Alkyl groups restrict the number of configurations amenable to hydrogen bonding, and this effect increases with the number and size of the alkyl groups surrounding O-H moieties.…”
Section: Resultsmentioning
confidence: 99%
“…The failure of AN to propagate LR-SIE confirms our conjecture, but the experiments in IPA appear to contradict it. However, we consider that the latter result represents a false negative because IPA, in contrast with H 2 O and MeOH, [49][50][51][52][53][54][55][56] lacks an extensive H-bond network. Alkyl groups restrict the number of configurations amenable to hydrogen bonding, and this effect increases with the number and size of the alkyl groups surrounding O-H moieties.…”
Section: Resultsmentioning
confidence: 99%
“…+ distance is calculated to be 1.20 Å, which is similar to the previous result from MP2/6-311+g(2d,2p) calculation yielding a symmetric hydrogen bond of length 2.38 Å with the proton located 1.19 Å from each oxygen. 43 In H + (CH 3 OH) 3 , the excess proton was located on the central methanol. In contrast to the neutral methanol cluster, the linear chain was the most stable conformation.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 It has therefore been thought that something similar could be occurring in the liquid phase and be responsible for its peculiar behavior. Several numerical simulations [18][19][20][21][22][23] and neutron diffraction experiments [24][25][26] have produced data that support this view. On the other hand, experimental results of neutron diffraction, 27,28 x-ray scattering, 29,30 and x-ray emission spectroscopy 31 have been taken to support the existence of cyclic clusters of methanol in the liquid phase.…”
Section: Introductionmentioning
confidence: 69%
“…Kashtanov et al 31 have suggested that numerical simulations could be using potentials that are not able to reproduce the hydrogen bonding network in ring structures. There is a substantial number of numerical simulations of methanol [18][19][20][21][22][23][32][33][34] and some of them which include polarizability [35][36][37][38] have shown the need for refined potentials.…”
Section: Introductionmentioning
confidence: 99%